Estimativa do potencial de produção de biomassa lenhosa residual nas sub-regiões terras de Trás-os-Montes e Aveiro - Godoy, Leandro Macedo (2020)
With the purpose of evaluating the potential of annual biomass production, statistical modeling was used based on Land Use and Land Cover (COS 2018) and 5thNational Forest Inventory data to simulate yield and growth of maritime pine in Terras de Trás-os-Montes sub-region (30.02 % off orest occupation) and eucalyptus in the Aveiro sub-region (77.24% of forest area) under different scenarios. A program (Stochastic Forest Simulator) was developed, where its base code comes from the AppTitude® software, having incorporated the equations of FlorNext® for maritime pine and the model GLOBULUS 3.0 for eucalyptus. The scenarios for maritime pine were built based in the Regional Forest Management Program of Trás-os-Montes and Alto Douro and for eucalyptus scenarios were built based on the variables used in the GLOBULUS 3.0 models. The conversion of the volume into biomass occurred through the especific massof the species and the residual biomass considering 28% of the volume for maritime pine and 25% of the volume for eucalyptus. The highest values of potential residual biomass from the stand of maritime pine wereobtained in scenarios where there wasno application of thinning, with the highest production in scenario 16 with 1.051.833,33 Mg at the end of the 50-year period of the simulations. The average residual biomass for the standing population in the first year represented 11,3% of the estimated annual consumption of 2.294.000 Mg of biomass in the country. The scenarios without thinning also showed the highest residual biomass values of finalcuts (CV = 1,27%). For thinning residues, the greatest results were observed in strong thinning interventions and several periods, with an average of 261,75 Mg in the first year and 3.600,65 Mg in the last simulated year. The scenario of higher potential residual biomass production for eucalyptus generated 699.417,97Mg (0,794Mg/m3) and 409.608,76 Mg (0,465Mg/m3).The highest residual biomass in final eucalyptus cuts at the end of the simulation period was 3.317.022,67 Mg and 1.942.588,84 Mg for the two especific massconsidered. The residual biomass in standing eucalyptus corresponds to 60,7% (higher especific mass) or 35,5% (lower especific mass) of national consumption in the first year of the simulations and the annual average of residual biomass from final cuts to 12,5% (higherespecific mass) or 7,3% (lower especific mass).